Cost-effectiveness of first line nivolumab-ipilimumab combination therapy for advanced non-small cell lung cancer: A systematic review and methodological quality assessment - Zaim, Remziye; Redekop, W. Ken; Uyl-de Groot, Carin A. (Frontiers in Health Services, 2023)
To assess the methodological quality of cost-effectiveness analyses (CEA) of nivolumab in combination with ipilimumab, we conducted a systematic literature review in the first-line treatment of patients with recurrent or metastatic non-small cell lung cancer (NSCLC), whose tumors express programmed death ligand-1, with no epidermal growth factor receptor or anaplastic lymphoma kinase genomic tumor aberrations. PubMed, Embase, and the Cost-Effectiveness Analysis Registry were searched, in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. The methodological quality of the included studies was assessed by the Philips checklist and the Consensus Health Economic Criteria (CHEC) checklist. 171 records were identified. Seven studies met the inclusion criteria. Cost-effectiveness analyses differed substantially due to the applied modeling methods, sources of costs, health state utilities, and key assumptions. Quality assessment of the included studies highlighted shortcomings in data identification, uncertainty assessment, and methods transparency. Our systematic review and methodology assessment revealed that the methods of estimation of long-term outcomes, quantification of health state utility values, estimation of drug costs, the accuracy of data sources, and their credibility have important implications on the cost-effectiveness outcomes. None of the included studies fulfilled all of the criteria reported in the Philips and the CHEC checklists. To compound the economic consequences presented in these limited number of CEAs, ipilimumab’s drug action as a combination therapy poses significant uncertainty. We encourage further research to address the economic consequences of these combination agents in future CEAs and the clinical uncertainties of ipilimumab for NSCLC in future trials.